2011
DOI: 10.1002/j.2048-7940.2011.tb00084.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Nurse-Led, Home-Based Pulmonary Rehabilitation in Patients with COPD in Turkey

Abstract: The goal of this study was to determine the effectiveness of nurse-led, home-based pulmonary rehabilitation in patients with stage 3 or 4 chronic obstructive pulmonary disease (COPD), according to the Global Initiative for COPD (GOLD) staging system. The study consisted of 32 patients--a nurse-led, home-based pulmonary rehabilitation group (16) and a control group (16). In the rehabilitation program, patients received education about their diseases and performed breathing exercises and lower- and upper-extremi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
91
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(97 citation statements)
references
References 13 publications
3
91
3
Order By: Relevance
“…Of these, 58 were considered potentially relevant and 23 studies 17,18,19,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50 met the eligibility criteria and were included in this review. One of the selected studies appeared in two distinct publications 49,50 in which the same intervention was applied to the same patients but describing different outcomes.…”
Section: Description Of Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Of these, 58 were considered potentially relevant and 23 studies 17,18,19,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50 met the eligibility criteria and were included in this review. One of the selected studies appeared in two distinct publications 49,50 in which the same intervention was applied to the same patients but describing different outcomes.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…Thirteen studies were done in Europe 17,19,21,31,33,38,42,43,45,46,48,49,50 , six in Asia 30,36,39,40,44,47 , two in Australasia 34,35 , one in North America 41 , and one in South America 32 . Among the studies included in the review, 19 17,18,19,30,31,32,33,34,36,38,39,40,42,43,44,46,47,48,49,50 compared HCPR to control group (n = total 893; n HCPR = 485), while four 35,37,41,45 compared HCPR to OPR (n total = 375; n HCPR = 178). No studies reported harmful effects related to HCPR during interventions.…”
Section: Description Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Nurses' treatment options and decision-making (DM) in severe breathlessness As seen in studies on the implementation of interventions [10][11][12][13] or in guidelines recommending interventions, 14 15 nurses' treatment options in breathlessness vary in different countries and settings, as do the duties and legal responsibility they have. Other issues include a lack of institutional support for specialised nurses, too little time and few possibilities for systematic reflection or supervision.…”
Section: Introductionmentioning
confidence: 99%